CARBON AND NITROGEN IN SOILS AND HUMIC FRACTIONS OF DIFFERENT PEDOFORMS IN THE ATLANTIC FOREST BIOME - Pereira, Marcos Gervasio Gervasio; Mendonça, Victoria Maria Monteiro; Santos, Gilsonley Lopes; Piccolo, Marisa de Cássia (Floresta, 2020)
Relief is a soil formation factor that can modify the distribution of soil organic matter (SOM) fractions in a landscape. The objective of this study was to evaluate the effect of the relief on SOM fractions, considering their distribution in different topographic positions, segments, in two pedoforms (concave and convex) in areas covered with forest in the Atlantic Forest biome. The two pedoforms were selected in adjacent areas and divided into segments considering the topographic variation. The carbon and nitrogen origins were evaluated in the extract up to 100 cm of depth. Soil samples from the 0-5, 5-10, and 10-20 cm layers were collected for chemical characterization and fractioning (granulometric and chemical) of the SOM. The soil density in the 0-5 and 5-10 cm layers was determined to calculated the carbon stocks. The isotopic composition showed predominance of 13C. The highest organic carbon and particulate carbon contents were found in the convex pedoform. The distribution of humic fractions showed that the larger part of the humidified carbon was in the humin fraction. The humin and fulvic acid fractions were higher in the convex pedoform. The carbon stocks were, in general, higher in the convex pedoform, decreasing as the soil depth increased; and nitrogen stocks presented no differences. The higher carbon and nitrogen contents were found in the convex pedoform and in the lower region of the concave pedoform.